STRATEGY IN DEVELOPING SUSTAINABLE BUFALLO BREEDING IN SOUTH SULAWESI - Anshar, M.; Rasjid, Sjamsuddin; Hasan, Syamsuddin (Proceeding Buffalo International Conference, 2013)
This research wasaimed at analyzing buffalo breeding sustainability in South Sulawesi,based on the assessment of sustainable index and status using Multidimensional Scaling (MDS). Data used were primary and secondary data. This research used the ordination technique to of the MDS method to find out the sustainable development index and status of several dimensions for buffalo breeding in South Sulawesi. The sustainable development index of the ecology dimension is 49.35%, which indicates a less sustainable status. The index for legal and Institutional (36.16%) as well as technology (43.50%) both also yield a status of less sustainable. The sustainable development index for the socio-cultural (51.64%) and the economic dimension (59.56%) both yield a status of sufficient sustainability.Â  An analysis on the existing conditions of five dimensions of buffalo breeding development in South Sulawesi resulted in an index of 48.06%, which falls under the less sustainable category. As a conclusion, in the current conditions of buffalo breeding in South Sulawesi, three dimensions namely ecology technology and constitution are classified as less sustainable, while the economic and socio-cultural dimension is already sufficiently sustainable. Therefore, more improvements are suggested towards dimensions with less sutainability.